Identifikasi Jenis Lepidoptera di Kecamatan Koto Tujuh, Kabupaten Sijunjung, Sumatera Barat - Kurnia Fitri, Dwi Rini; Agustina, Nadia (Biospecies, 2024)
Butterflies were part of the Lepidoptera has an important role as a bioindicator of environmental change. This study aims to identify the types of Lepidoptera found in Kec. Koto Tujuh, Kab. Sijunjung, West Sumatra. We used the survey method with a purposive sampling technique divided into three zones: residential, forest edges, rice fields and plantation. We found 23 species of Lepidoptera belonging to five families, namely Nymphalidae (11 species), Lycaenidae (1 species), Papilionidae (4 species), Hesperiidae (2 species), and Pieridae (5 species), with the total number 59 individuals.